ANALISIS KEPADATAN LAPIS PONDASI AGREGAT KELAS A PADA PEKERJAAN JALAN LINTAS SELATAN LOT 3 P. SERANG – SUMBERSIH BLITAR STA 4+125 – 4+225 LAJUR KIRI - R Adam Sulaiman Raden; Believa Satria Wicasa; Nugroho Utomo (LPPM Universitas Abdurrab, 2026)
This study analyzes the density of Class A aggregate base course (LPA) on the South Cross Road (JLS) Lot 3 P. Serang–Sumbersih Blitar project, left lane STA 4+125–4+225, focusing on compliance with specified density standards. A descriptive quantitative approach was applied using field density test data from the sand cone method at three points: STA 4+125 L, STA 4+175 L, and STA 4+225 L. Results yielded wet unit weight, moisture content, and dry unit weight values compared to the maximum dry unit weight plan (100% density). STA 4+125 L and 4+175 L achieved 100.44% and 101.71% (moisture 9–11%), meeting and slightly exceeding specifications; STA 4+225 L reached only 94.18% (moisture 18%), due to suboptimal heavy equipment compaction, posing a potential weak point in the pavement structure. Recommendations include material replacement, drying and re-compaction after moisture adjustment, or cement stabilization to Cement Treated Base (CTB).